2015
DOI: 10.1021/acscatal.5b00488
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Catalytic CO Oxidation over Co3O4 Nanowires by Substituting Co2+ with Cu2+

Abstract: Co 3 O 4 is an attractive earth-abundant catalyst for CO oxidation, and its high catalytic activity has been attributed to Co 3+ cations surrounded by Co 2+ ions. Hence, the majority of efforts for enhancing the activity of Co 3 O 4 have been focused on exposing more Co 3+ cations on the surface. Herein, we enhance the catalytic activity of Co 3 O 4 by replacing the Co 2+ ions in the lattice with Cu 2+ . Polycrystalline Co 3 O 4 nanowires for which Co 2+ is substituted with Cu 2+ are synthesized using a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(120 citation statements)
references
References 29 publications
6
114
0
Order By: Relevance
“…[10,15,50,51] In contrast, some researchers revealed that the CO oxidation reactionm echanism can follow the LH mechanism, which includes the main four steps in CO oxidation:1 )COa dsorption on the cationic metal sites, 2) the formation of active oxygen that resultsf rom O 2 molecules adsorbed on oxygen vacancies, 3) the reaction of CO with active oxygen, and 4) CO 2 desorption from the catalyst surface. [10,15,50,51] In contrast, some researchers revealed that the CO oxidation reactionm echanism can follow the LH mechanism, which includes the main four steps in CO oxidation:1 )COa dsorption on the cationic metal sites, 2) the formation of active oxygen that resultsf rom O 2 molecules adsorbed on oxygen vacancies, 3) the reaction of CO with active oxygen, and 4) CO 2 desorption from the catalyst surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10,15,50,51] In contrast, some researchers revealed that the CO oxidation reactionm echanism can follow the LH mechanism, which includes the main four steps in CO oxidation:1 )COa dsorption on the cationic metal sites, 2) the formation of active oxygen that resultsf rom O 2 molecules adsorbed on oxygen vacancies, 3) the reaction of CO with active oxygen, and 4) CO 2 desorption from the catalyst surface. [10,15,50,51] In contrast, some researchers revealed that the CO oxidation reactionm echanism can follow the LH mechanism, which includes the main four steps in CO oxidation:1 )COa dsorption on the cationic metal sites, 2) the formation of active oxygen that resultsf rom O 2 molecules adsorbed on oxygen vacancies, 3) the reaction of CO with active oxygen, and 4) CO 2 desorption from the catalyst surface.…”
Section: Discussionmentioning
confidence: 99%
“…[10,15,50,51] In contrast, some researchers revealed that the CO oxidation reactionm echanism can follow the LH mechanism, which includes the main four steps in CO oxidation:1 )COa dsorption on the cationic metal sites, 2) the formation of active oxygen that resultsf rom O 2 molecules adsorbed on oxygen vacancies, 3) the reaction of CO with active oxygen, and 4) CO 2 desorption from the catalyst surface. According to previous studies, [9,10,15] the choice of as uitable doping cation can create structurald efects and residual stress as well as oxygen vacancies. These previous studies suggested that there are no clear reaction mechanisms on certain catalysts for CO oxidation and that tuningt he surface structurald efects (CO adsorption and the formation of active oxygen) of am aterial should be an efficient method to design new catalysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the S2p spectrum, the peak for sulfate ion of SO4 2-was confirmed at 169.7 eV. Compared to the peak positions between the Co/Al2O3 and Co/SO4 2-/Al2O3 catalysts before the de hydrogenation, the peak of cobalt species was slightly 20) . This phenomenon might derive from the interaction between sulfated ion (SO4 2-) and cobalt element to form CoSO4-like species.…”
Section: Catalyst Surfacementioning
confidence: 90%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Up to now, many highly efficient catalysts for CO oxidation, mainly including supported noble metals (such as Au and Pt) 8,9,11,12,[19][20][21][22][23][24][25] and metal-oxides (such as Co 3 O 4 and MnO 2 ) have been successfully developed. 7,[13][14][15][16][17][18][26][27][28][29][30][31][32][33] For example, TiO 2 -supported Au catalyst is very active for CO oxidation at the temperature of −70 C. 19-21 SiO 2 -supported Pt-Fe catalysts give almost 100% CO conversion and 100% CO selectivity at room temperature. 8 Metal oxides are less expensive compared with supported noble metals, which enhances their potential for practical applications.…”
mentioning
confidence: 99%